Cesarean Section Trends In The Tertiary Hospital – A Description Study With The Robson Classification - Armi, Wendy (Fakultas Kedokteran Universitas Andalas, 2023)
Introduction: The high incidence of Cesarean Section (CS) in Indonesia causes morbidity andmortality for mothers and babies and is not in line with efforts to reduce maternal and infant mortalityaccording to the 2024 RPJMN. This study aims to provide an overview of the criteria for C-sectionaccording to the Robson Group Classification System for CS indications at the suburban area level.Methods: his study used medical record data from patients who underwent childbirth at RSIAPermata Bunda, Solok City, West Sumatra, from July to December 2021, where each patient wasincluded in the CS criteria group according to the Robson Group Classification System for CSindications. After that, all data groups were analyzed.Results: The CS rate at RSIA Permata Bunda for the period July 2021-December 2021 is 80.65%.This is in accordance with tiered referral conditions at level 1 health facilities.In the CS Robson criteria, criterion 5 occupies the highest position in the percentage of AbsoluteContribution (29.08) and Relative Contribution (36.05). This criterion includes all multiparousdeliveries, singleton fetuses, and pregnancies >37 weeks with at least 1 history of uterine surgery(uterine scar).In the Robson 2 group, Absolute Contribution (18.33) and Relative Contribution (22.73) were thesecond highest. This group includes all nulliparous pregnancies with singletons, >=37 weeks, with anindication for induction or surgery prior to delivery.Conclusion: The Robson Group Classification System for CS indications is considered to be used indetermining the description of CS criteria in tertiary hospitals. This criterion can well help theHospital to describe and analyze the high rate of C-section